LEADERSHIP STYLES OF UNIVERSITY LIBRARIANS IN PUBLIC UNIVERSITY LIBRARIES IN RIVER STATE, NIGERIA (NAU Journal of Library and Information Science, 2025)
This study investigated leadership styles employed by university librarians in public university libraries in Rivers State, Nigeria. The study adopted a descriptive survey research design. The population of the study was made up of 67 librarians in three public university libraries in Rivers State, Nigeria. Data was gathered using a questionnaire and analyzed using simple frequency and percentage techniques with the Statistical Package for the Social Sciences (SPSS version 22). Findings reveal democratic leadership (38.8%) and transformational leadership (31.3%) are the most common leadership styles. Also, majority of library staff (73.1%) accept that leadership styles influence the positive organizational culture for an overall constructive and supportive work environment. This study concluded that the leadership style of librarians in public university libraries in Rivers State is participative and transformational.
Keywords: Leadership, Librarians, Public University, Libraries, Rivers State, Nigeria